Economic and Legal Instruments for Ensuring the Financing of Ukraine's Reconstruction Projects: Legal and Regulatory Analysis - Teremetskyi, Vladyslav; Dovhan , Viktor (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
In light of the significant consequences of the russian-Ukrainian war, the issue of legislatively implementing reliable mechanisms for financing Ukraine's reconstruction projects has become highly relevant. In this context, the study and evaluation of regulatory acts within the system of economic and legal instruments for financing such projects are of critical importance.Based on an analysis of existing sources, the scope and degree of legal development of economic and legal instruments for financing Ukraine's reconstruction projects have been identified. The necessity of creating and implementing a comprehensive legislative and regulatory framework, which requires high-quality scientific support, has been emphasized. It is noted that such a framework is being established in Ukraine for the first time since its independence.It is proposed to systematize regulatory legal acts within a three-tier system encompassing international, national, and regional levels. Additionally, the necessity of systematizing regulatory legal acts in the context of two models of post-war recovery in Ukraine has been substantiated:Compensatory model: involves reimbursing owners for destroyed or damaged property, aligning with a traditional approach;Innovative model: focuses on creating a fundamentally new economy based on modern technological foundations.It is concluded that economic and legal instruments for financing reconstruction projects have not yet been identified as a distinct category nor defined in either Ukrainian legislation or legal science. Emphasis is placed on the need for systematizing economic and legal instruments based on various criteria, as well as on the necessity of developing tools to ensure rapid and effective post-war recovery in Ukraine.Particular attention is drawn to the importance of identifying gaps in legal regulation and creating conditions for their elimination to improve the efficiency of financing reconstruction projects.